The appropriateness of ceftriaxone utilization in government hospitals of Eastern Ethiopia: A retrospective evaluation of clinical practice - Firehiwot Amare; Tigist Gashaw; Mekonnen Sisay; Yohannes Baye; Tewodros Tesfa (SAGE Open Medicine, 2021)
Introduction: Drug use evaluation is a method of obtaining information to identify problems related to drug use and if properly developed, a means of correcting the problems. Ceftriaxone is among the most commonly utilized cephalosporins. Owing to a broad spectrum of activity and being used empirically, ceftriaxone has been used inappropriately posing a risk for development of antimicrobial resistance. This study is, therefore, designed to evaluate the appropriateness of ceftriaxone utilization in government hospitals in Harar town. Methods: A retrospective cross-sectional study was conducted in four government hospitals of Harar town by reviewing the medical records of 271 patients who received ceftriaxone from 1 January to 31 December 2016. Systematic random sampling was utilized to capture the medical records. Data were entered and analyzed using SPSS version 22. Results: From the 271 medical records reviewed majority of patients were from surgical ward ( n  = 85, 31.4%) followed by gynecology and obstetrics ward ( n  = 67, 24.7%). Demographically, the majority of the patients were female ( n  = 142, 52.4%). Patients in the age group of 20–29 years were dominant ( n  = 98, 36.2%). A total of 71 drugs were co-administered with ceftriaxone, the most common being metronidazole followed by tramadol. Among the co-administered drugs, unfractionated heparin ( n  = 6), warfarin ( n  = 5), and enoxaparin ( n  = 1) were found to have a moderate drug interaction with ceftriaxone. Ceftriaxone was commonly used for post-operative prophylaxis ( n  = 80, 27.5%) followed by for the management of pneumonia ( n  = 62, 21.3%). The result of ceftriaxone use evaluation showed that majority ( n  = 190, 70.1%) were found to be inappropriate. The inappropriate utilization was primarily due to wrong indication (indications for which ceftriaxone was not the primary option) ( n  = 114, 60.0%) followed by wrong duration ( n  = 54, 28.4%). Conclusion: Ceftriaxone was used inappropriately in more than two-thirds of the patients, with wrong indication and wrong duration contributing the majority. Inappropriate use of antibiotics may potentially lead to the emergence and spread of drug-resistant microorganisms and also ultimately exposes the patient to treatment failure, prolonged hospital stay, and higher cost of therapy.